Development ethics, deliberative democracy and environmental citizenship. The global challenge of sustainability - Villarroel, Raúl (Acta Bioethica, 2013)
This article explores the notion of "citizenship" from the theoretical context deployed by ecological problems, taking into account the findings and challenges posed to the figure of citizenship by the alleged existence of a phenomenon of environmental anthropogenic devastation as it is hold affects the planet in our days. Some considerations about "environmental citizenship" are outlined in order to allow the progress of this particular reflection, assuming that the contemporary political philosophical literature presents various theoretical scopes that could be addressed in this regard, especially considering that they try to enlarge the canonical concept of citizenship initially presented by Marshall.